EXPLORATION OF TEACHER READINESS IN MATHEMATICS LEARNING AT THE MERDEKA CURRICULUM IN BRAWIJAYA SMART SCHOOL (BSS) JUNIOR HIGH SCHOOL MALANG - Setianingsih, Tri; Islamiyah, Makhabbatul; Mukti, Taufiq Satria (Proceeding of International Conference on Islamic Education (ICIED), 2022)
Efforts to change the curriculum in the context of accelerating recovery in the field of education in the post-pandemic era are contained in the policies of the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia as indicated by the presence of the "Merdeka" curriculum. The role of the teacher in the Merdeka curriculum is very important in order to achieve the desired curriculum goals. Therefore, teachers also need readiness in implementing an Merdeka curriculum. The research was conducted qualitatively with a case study conducted at the Brawijaya Smart School Junior High School (SMP BSS) Malang on mathematics teachers. Several characteristics and policies of the Merdeka curriculum will be analyzed how much the readiness of teachers and the challenges faced in implementing the Merdeka curriculum will be analyzed.